Coordenação entre as respostas da catalase e da ascorbato peroxidade em folhas de feijão caupi submetidas a diferentes fontes de peróxido de hidrogênio - Silva, Ivanice Bezerra da (2012)
The plants are often exposed to variations in environmental conditions that may trigger metabolic disturbances leading to a consequent loss in productivity of crops. These stressful conditions usually induce an accumulation of reactive oxygen species (ROS) in the cell, a condition known how oxidative stress. Among these species, hydrogen peroxide (H2O2) is an important molecule involved in numerous signaling mechanisms. The present study aimed to understand the relationship between the different enzymatic mechanisms of elimination of H2O2 by catalase (CAT) and ascorbate peroxidase (APX) in leaf tissues of seedlings of the species Vigna unguiculata L. Walp, under conditions of oxidative stress induced by application of CAT inhibitor, 3-amino-1,2,4-triazole (3-AT), and H2O2 itself on the roots. Three experiments were conducted. The first experiment was performed applying the compound 3-AT (5 mM) during the time (hours). In the second experiment, seedlings were exposed to different concentrations of H2O2 (2.5, 5.0, 7.5, 10 mM) for 48 h. The third strategy included the pre-treatment with H2O2 (2.5 mM) for 24 h, followed by subsequent treatment with the inhibitor 3-AT and recovery control condition. Treatment with 3-AT causes a strong inhibition of CAT activity in leaf tissues accompanied by an increase of activity of APX. However a decrease in oxidative damage to lipids is not observed as indicated by TBARS. It was observed that activity of APX is directly linked to the content of peroxide. Inductions in the activities of CAT and APX were observed mainly in the seedlings treated with 2.5 mM H2O2. This can be associated with a decrease in oxidative damage to lipids. In contrast, one same tendency was not observed in treatments with higher concentrations of this ROS. These results suggest that the concentration of 2.5 mM H2O2 can induce responses antioxidants later in seedling cowpea. This concentration when applied as pre-treatment for 24 h promoted an induction systems removers CAT and APX, both in activity and in terms of gene expression. However this increment was not observed in the recovered plants and the plants subsequently subjected to 3-AT. Additionally, the pretreatment was not sufficient to attenuate the inhibition of CAT activity and oxidative damage to lipids caused by the subsequent application of this inhibitor. The results showed that the application of 3-AT and H2O2 in the root systems of seedlings of cowpea promote changes in the parameters analyzed in leaf tissues that indicate a direct response to the presence of these factors or systemic signaling mecanisms. H2O2 appears to activate the responses of two antioxidant systems in this study thar does not promote greater protection in case of additional treatment with 3-AT. This demonstrates the importance of the CAT system. In this work, complete results indicate that there is a difference between the signaling and the effects caused by exposure to H2O2 and by treatment with 3-AT